Controlled "off–on" fluorescent probe for the specific detection of hyperhomocysteinemia. Issue 8 (22nd January 2021) - Zheng, Jinrong; Li, Jianlong; Luo, Hongli; Sun, Lingbin; Sang, Mangmang; Yu, Xiu
Abstract : An Hcy-specific fluorescent probe (HSFP) with excellent selectivity and anti-interference capability was developed for the detection of hyperhomocysteinemia. Abstract : Hyperhomocysteinemia is an established risk factor for atherosclerosis and vascular disease. Therefore, designing a hyperhomocysteinemia specific probe is of great significance for the early warning of cardiovascular diseases. However, developing probes that can efficiently and specifically recognize homocysteine (Hcy) remains a tremendous challenge. Therefore, we designed an Hcy-specific fluorescent probe (HSFP) with excellent selectivity and anti-interference capability. Interestingly, this probe can automatically "off–on" in water solution, but the fluorescence of HSFP remains "off" when Hcy is present in the solution. The spectroscopic data demonstrated that the fluorescence of HSFP attenuated 13.8 folds toward Hcy in water without interference from other biothiols and amino acids. Furthermore, HSFP can sensitively reflect the change of Hcy content in cells. Therefore, HSFP was further applied to detect hyperhomocysteinemia in vivo with high efficiency. In summary, we have developed an Hcy-specific fluorescent probe to efficiently detect Hcy in vivo and in vitro, which may contribute to basic or clinical research.